Unveiling ethical foundations: integrating lessons from Quranic narratives of 'Ad and Thamud into built environment education - Mohd Basri, Mohd Rafaei; Aling, Nor Azizah; Abdul Ghaffar, Ahmad Fathi (Asian Scholars Network (ASNet), 2025)
In the field of built environment education, there is a growing recognition of the need for pedagogical methods that go beyond technical knowledge to include broader ethical and societal dimensions. Thus, this study explores the moral teachings within Quranic narratives, specifically focusing on the stories of 'Ad and Thamud, to extract insights relevant to the built environment. This initiative is expected to foster cultural sensitivity, enhance professional practice, and contribute to scholarly discourse in both built environment education and religious studies. Ultimately, by uncovering ethical foundations and incorporating timeless wisdom from Quranic narratives, this study aims to address critical gaps in pedagogical approaches and advance the field of built environment education. Hence, the study's objectives include examining these Quranic stories, extracting pertinent lessons, contextualizing them within built environment education, and formulating actionable recommendations. Using qualitative content analysis, Quranic verses related to the narratives of 'Ad and Thamud are analysed for themes relevant to urban planning, sustainability, environmental stewardship, social justice, and ethical leadership. These themes are synthesized to highlight their relevance within built environment education. The outcomes of this study offer a deeper understanding of the ethical and societal dimensions within the built environment discipline. Recommendations for educators and curriculum developers are provided to facilitate the seamless integration of these insights into educational frameworks.